Phenotype from SAMD9 Mutation at 7p21.2 Appears Attenuated by Novel Compound Heterozygous Variants at RUNX2 and SALL1 - Sills, E. Scott; Wood, Samuel H. (Global Medical Genetics, 2021)
Sterile α motif domain-containing protein 9 (SAMD9) is a regulatory protein centrally involved in cell proliferation and apoptosis. Mapped to 7p21.2, variants in SAMD9 have been reported in <50 pediatric cases worldwide, typically with early lethality. Germline gain-of-function SAMD9 variants are associated with MIRAGE syndrome (myelodysplasia, infection, restricted growth, adrenal hypoplasia, genital anomalies, and enteropathy). Spalt like transcription factor 1 (SALL1) is a zinc finger transcriptional repressor located at 16q12.1 where only two transcript variants in SALL1 are known. RUNX2 (6p21.1) encodes a nuclear protein with a Runt DNA-binding domain critical for osteoblastic differentiation, skeletal morphogenesis, and serves as a scaffold for nucleic acids and regulatory factors involved in skeletal gene expression. RUNX2 and SALL1 are thus both “master regulators” of tissue organization and embryo development. Here, we describe exome sequencing and copy number variants in two previously unknown mutations—R824Q in SAMD9, and Q253H in SALL1. A multiexon 3′ terminal duplication of RUNX2 not previously encountered is also reported. This is the first known phenotype assessment for an intersection of all three variants in a healthy 46,XX adult. Focusing on developmental progress, ultrastructural renal anatomy, and selected reproductive aspects, we describe this unique genotype diagnosed incidentally during coronavirus disease 2019 (COVID-19) illness. Individually, disruption in SAMD9, RUNX2, or SALL1 would be expected to give a bleak prognosis. However, this variant convergence appears to dampen severe pathology perhaps by cross-gene silencing of effects normally deleterious when such changes occur alone.
Keywords: SAMD9; RUNX2; SALL1; phenotype; renal structure